Effects of Extraction Method on Yield, Phenolic and Flavonoid Content of Leaf, Stem and Root of Cassia alata Linn - Scholastica Ramih, Bunya; Samuel, Lihan (UNIMAS Publisher, 2024)
The study of medicinal plants has gained significant interest among researchers because of their potential for therapeutic purposes and the production of natural drugs. In Sarawak, Cassia alata is one of the native plants used for medicinal purposes, such as treatment for constipation, ringworm, and other skin diseases. This study determined the yield of extraction, total phenolic content (TPC), and total flavonoid content (TFC) of the leaf, stem, and root of C. alata using various extraction methods and solvent extractions. The extractions were performed using soxhlet extraction (SE) and ultrasonic-assisted extraction (UAE) with ethanol and chloroform. Among all, the extract obtained from SE with ethanol solvent (SE-EtOH) showed the highest yield in all plant parts (leaf: 28.62 %, stem: 10.06 %, and root: 9.79 %). Meanwhile, the TPC and TFC estimated using the FolinCiocalteu phenol reagent and aluminium chloride colorimetric assay methods showed that the highest TPC and TFC were from the leaf extract obtained using UAE and chloroform (UAE-Chlo-L) with a TPC value of 117.436 mg GAE/g DW and a TFC value of 568.778 mg QE/g DW, respectively. Overall, the findings demonstrated that chloroform was an effective solvent system for all plant parts on the TPC and TFC, with the leaf part containing the greatest value, and that ultrasonic-assisted extraction was the best approach. This exploration is beneficial for the determination of methods that produce optimum yield, phenolic, and flavonoid content in C. alata’s species.